CT Scan in Abdominal Emergency Surgery (Hot Topics in Acute Care Surgery and Trauma,, 2018)
This book focuses on the diagnostic impact of CT scans in severe abdominal trauma and in non-traumatic acute abdomen, the two clinical entities that constitute the main reasons for referrals for this imaging technique from the intensive care unit. The concept behind it is that emergency surgeons and physicians not only need the clinical knowledge to manage the different pathological conditions, but that they must also have a full understanding of diagnostic imaging modalities. To this end, each chapter includes a description of a specific acute abdominal disorder. In addition to the clinical presentation and the diagnosis and management guidelines, there is a special focus on imaging studies with clear and concise descriptions, high-quality images and the evolution grading scale to aid interpretation. This easy-to-read book is an ideal source of practical information for acute care surgeons, radiologists and for all the members of the emergency team. .